IMPLEMENTASI PEMENUHAN HAK PENGURANGAN MASA PIDANA BAGI NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS II A PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN - Galingging, Winda Rosmauli Br; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Remission is a motivation for prisoners to always behave well, and no less important is remission as a catalyst and one of the benchmarks of successful coaching in correctional institutions / detention. Reduction of the period of serving a criminal given to convicts and child criminals who meet the conditions specified in the legislation. This is as stated in Article 1 number 6 Government Regulation (PP) No.32 of 1999 concerning the Requirements and Procedures for the Implementation of the Rights of Prisoners. But in the service of granting the right to reduce the criminal period in prison is not well taken care of by authorized officials. Finally, many prisoners do not get their rights.This type of research is classified as sociological research, because in this study the author directly conducts research at the location or place in order to provide a complete and clear picture of the problem under study. This research was conducted at Class II A Penitentiary Pekanbaru , while the population and sample are all parties related to the problem examined in this study, the source of the data used, primary data, and secondary data, and tertiary data, the data collection techniques in this study were carried out by interview, and literature study.This study aims to find out how the implementation of the fulfillment of the right to reduce the criminal period for prisoners in Class II A Penitentiary Pekanbaru, what obstacles faced by the Penitentiary in implementing the fulfillment of the right to get a decent criminal period reduction for prisoners in Class II A Penitentiary Pekanbaru and efforts what is done by Class II A Penitentiary Pekanbaru in overcoming the inhibiting factors in fulfilling the right to reduce criminal periods for prisoners.Keywords: Compliance- Reduction of Criminal Period-Prisoners.